Karakteristik Hubungan Balok-Kolom Beton Berserat Akibat Pembebanan - Kurniawan, Rendy Yudha; Yoresta, S.T.,M.T., Dr. Eng. Fengky Satria (Universitas Teknokrat Indonesia, 2024)
Fibrous concrete material can improve the performance of beam-column connections characteristics. This study aims to determine the effect of addition of palm fibers, coconut fibers, and wire bendrat to the performance of the Beam- Column connection due to loading. The method applied in this study was experimental with test sample used in the form of T-shaped columns with the size of cross section of the beam (200 x 120) mm and the size of the cross-sectional area of the column (120 x 130) mm. Test sample total is 4 pieces, the first test sample is the control which is not given additional fiber, and the other three test samples are given the addition of palm fibers, coconut fibers, and wire bendrat each 1% of the volume of sample. The test results showed that the tensile load maximum fiber highest was obtained in bendrat wire test sample that was 21.3 kg. The result of beam-column connections concrete showed that beam-column connection coconut fibrous concrete test of has maximum acceptance value and lowest rigidity of 636 kg and 460 kg/mm. In contrast to its maximum dactality and deflection value, the beam-column connection concrete coconut fiber test sample increased the highest ductality and maximum deflection value of 1.77 and 7.9 mm.